1998
DOI: 10.1046/j.1365-2761.1998.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular lesions associated with attachment of the parasitic copepod Ommatokoita elongata (Grant) to corneas of Greenland sharks, Somniosus microcephalus (Bloch & Schneider)

Abstract: The eyes from six Greenland sharks, Somniosus microcephalus (Bloch & Schneider), infected with the parasitic copepod Ommatokoita elongata (Grant) were collected in the Arctic waters of Victor Bay, North‐west Territories, Canada, for study. Transformed adult female copepods, one per eye, were firmly attached to the corneas by an anchoring structure (i.e. the bulla) and each bulla was associated with an opaque area on the cornea. Two eyes additionally had one O. elongata copepodid attached to the cornea via fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 6 publications
1
40
1
1
Order By: Relevance
“…The high prevalence and low intensity of infection observed for 0. elongata on the eyes of Pacific sleeper sharks is similar to observations reported concerning infections of this parasite on the eyes of Greenland sharks (see Berland, 1961;Borucinska et al, 1998). How the typical attachment pattern of 1 adult female per eye is achieved remains a mystery; however, results of this study as well as those of Borucinska et al (1998) indicate that it is not unusual for individual sleeper shark eyes to be concomitantly infected by 1 adult female and 1 to several larvae of O. elongata.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The high prevalence and low intensity of infection observed for 0. elongata on the eyes of Pacific sleeper sharks is similar to observations reported concerning infections of this parasite on the eyes of Greenland sharks (see Berland, 1961;Borucinska et al, 1998). How the typical attachment pattern of 1 adult female per eye is achieved remains a mystery; however, results of this study as well as those of Borucinska et al (1998) indicate that it is not unusual for individual sleeper shark eyes to be concomitantly infected by 1 adult female and 1 to several larvae of O. elongata.…”
Section: Discussionsupporting
confidence: 88%
“…Benz et al (1998) reported the eyes of some Pacific sleeper sharks in the eastern Pacific to be infected with the parasitic copepod Ommatokoita elongata (Grant, 1827) (Lernaeopodidae: Siphonostomatoida) and noted gross eye lesions associated with infections. Borucinska et al (1998) examined lesions associated with O. elongata infections in Greenland sharks and concluded that these parasites can cause eye damage resulting in vision impairment including partial blindness. However, these same authors also concluded that 0. elongata infections do not significantly debilitate Greenland sharks and that this may be because this host species does not rely on keen vision.…”
mentioning
confidence: 99%
“…George's gateway interest to sleeper sharks was, naturally, in its parasitic copepods. The lernaeopodid Ommatokoita elongata embeds its bulla (attachment structure) in the cornea of the Greenland shark, and the resulting lesion causes corneal opacity or near blindness in chronic infections, with the prevalence of infection being typically high and each shark typically having a single female O. elgonata attached to each eye (Borucinska et al 1998, Borucinska and. George also was captivated by the fact that despite the shark being regarded as a sort of toothed manatee, slow moving, oafi sh, and visually-impaired if infected with O. elongata, it was known to harbor seal parts plus swiftswimming fi shes in its stomach.…”
Section: It Was Time For Questions From the Panel I Believe George mentioning
confidence: 99%
“…Will this cause impaired vision, and will the shark suffer from it? Several studies have investigated how O. elongata affects the corneas of Somniosus spp., and how vision could be affected (Benz et al 2002;Borucinska, Whiteley, and Benz 1998). Although these sharks may go partially blind, this does not affect their ability to survive.…”
Section: Tunu-vimentioning
confidence: 99%